2020
DOI: 10.3390/pharmacy8030144
|View full text |Cite
|
Sign up to set email alerts
|

Stigma of Opioid Use Disorder and Its Indirect Effects on Student Pharmacists’ Perceptions and Attitudes

Abstract: Objectives: Pharmacists play a vital role in serving patients during the ongoing nationwide opioid epidemic, and so it is also critical to educate the next generation of pharmacists on opioids and opioid use disorder (OUD). The primary objective of this study was to quantitatively characterize student perceptions of opioid use and the stigma associated with OUD. Secondary aims were to determine whether differences in perceptions exist based upon the student’s year in the Doctor of Pharmacy program or employmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Previous studies utilizing similar qualitative methods have been employed to identify perceptions and experiences of stigma within clinical settings such as nursing students (Lewis & Jarvis, 2019) and pharmacy students (Hall, et al, 2020) or by individuals with substance use experience and medication-assisted treatment patients (Earnshaw et al, 2019;Hall, et al, 2021). However, using qualitative studies to identify stigma-reduction strategies by individuals with lived experience of substance use is limited, and the few available studies have primarily focused on medication-assisted treatment stigma reduction (Woo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies utilizing similar qualitative methods have been employed to identify perceptions and experiences of stigma within clinical settings such as nursing students (Lewis & Jarvis, 2019) and pharmacy students (Hall, et al, 2020) or by individuals with substance use experience and medication-assisted treatment patients (Earnshaw et al, 2019;Hall, et al, 2021). However, using qualitative studies to identify stigma-reduction strategies by individuals with lived experience of substance use is limited, and the few available studies have primarily focused on medication-assisted treatment stigma reduction (Woo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…24 Another cohort survey conducted at the University of Tennessee on pharmacy students did not seem to reveal stigmatizing attitudes towards the opioid-seeking behaviors of patients or classmates. 25 This difference might be attributable to setting differences between the two studies and the current study. On the contrary, a study done by Werremeyer et al demonstrated pharmacists' higher preference for social distancing (negative attitude) towards patients with opioid misuse behaviors.…”
mentioning
confidence: 74%
“…An 18-item survey was delivered electronically as previously published [ 15 ] in accordance to methodology derived from Dillman and colleagues [ 16 ]; seven closed-ended questions from this original survey item pertained to perceptions of naloxone use that have not been published previously ( Supplementary Materials ). All data were aggregated such that no personal information linking specific responses to a specific participant was retained.…”
Section: Methodsmentioning
confidence: 99%